The concepts of funding and financing when developing projects through public private partnerships (PPP) - Villalobos Carballo, Federico (2025)
The main objective of Public Private Partnerships (PPP) models is to generate efficiency gains throughout the project lifecycle. However, in a budget- constrained environment, PPPs are viewed as a tool for developing the projects which the government able to finance. That said, it is important to distinguish the concepts of project funding and projectfinancing.Funding refers to the sources of income to repay for the project investments during its life: taxes and tariffs. Financing refers to money invested. Broadly speaking, financing could take the form of public debt, private debt or private equity. Therefore, private money is not "free money" and funding will be needed to repay for it. Having a clear understanding of these elements is crucial within the decision-making process in public infrastructure development.